2009
DOI: 10.1111/j.1460-9568.2009.06626.x
|View full text |Cite
|
Sign up to set email alerts
|

Geometry and landmark representation by pigeons: evidence for species‐differences in the hemispheric organization of spatial information processing?

Abstract: In this study, we investigated how pigeons (Columba livia) represent environmental geometry and landmark information. Birds learned to locate the centre of a square arena by means of geometric cues alone, or by means of both geometric and landmark cues. By manipulating the type of information available at training and testing, we assessed which cues the birds had encoded, and through the use of monocular occlusion we examined how the information was represented by the two brain hemispheres. Our results show th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 39 publications
2
9
0
Order By: Relevance
“…For example, Wilzeck et al (2009) demonstrated that pigeons show a diVerent pattern of geometric encoding than chicks relative to the way the two hemispheres represent information. More investigation is necessary in order to determine whether chicks and pigeons are using similar strategies of spatial information processing but with diVerent hierarchal preferences, or whether the several million years of separate evolutionary paths followed by these two species has led to distinctly diVerent ways of encoding geometric information.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Wilzeck et al (2009) demonstrated that pigeons show a diVerent pattern of geometric encoding than chicks relative to the way the two hemispheres represent information. More investigation is necessary in order to determine whether chicks and pigeons are using similar strategies of spatial information processing but with diVerent hierarchal preferences, or whether the several million years of separate evolutionary paths followed by these two species has led to distinctly diVerent ways of encoding geometric information.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies on geometric encoding have signiWcantly expanded our knowledge on how animals encode and use the geometry of their environments in several ways, including the encoding of relative versus absolute metrics (e.g., Tommasi and Vallortigara 2000;Kelly and Spetch 2001;Gray et al 2004;Gray and Spetch 2006;Wilzeck et al 2009) and local versus global cues (e.g., Della Chiesa et al 2006a, b).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Even among vertebrate animals, different neurally based models might be necessary. For example, birds show hemispheric specializations in using geometric and nongeometric cues, patterns that differ across species (Vallortigara, Pagni, & Sovrano, 2004;Wilzeck, Prior, & Kelly, 2009). Sheynikhovich et al's model involves learning and could perhaps be applied to models of change over short-term experience, but it has not made any attempt to deal with development over the longer term.…”
Section: Critiquementioning
confidence: 99%
“…Local searching strategies are often associated with absolute distance encoding from spatial cues in a scene (vector strategy). Pigeons trained to locate a food reward at the centre of an arena tend to focus their searches at approximately the same distance from the walls in an expansion test (Wilzeck et al 2009). Comparable findings have been obtained in an array of freestanding objects of a similar geometric shape (Kelly et al 2008).…”
Section: Lateralization Of Familiar Landmark-based Navigationmentioning
confidence: 99%